2018
DOI: 10.3233/jad-170946
|View full text |Cite
|
Sign up to set email alerts
|

Early Detection of Alzheimer’s Disease Based on the Patient’s Creative Drawing Process: First Results with a Novel Neuropsychological Testing Method

Abstract: Based on the knowledge of art therapy, we developed a new neuropsychological drawing test in order to identify individuals with mild cognitive impairment (MCI) as well as dementia patients and healthy controls (HC). By observing a variety of drawing characteristics of 92 participants with a mean age of 67.7, art therapy and dementia experts discriminate HC from MCI, early dementia of the Alzheimer-type (eDAT), and moderate dementia of the Alzheimer-type (mDAT) by the process analysis of tree drawings on a digi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Comparable to the study design of Heymann et al (2018), a blinded-randomized analysis of the video material by a total of 56 experts from the fields "Gardening and landscape design" (GL) (n = 17, 3 female Mean age: 26.53 years); "Psychology and psychotherapy" (PP) (n = 15; 9 female; mean age: 23.07) and "Art therapy and Theater Pedagogy" (AT) (n = 24; 18 female; mean age 24.67 years) was conducted. In a first step, the topic of the discussion was introduced to the experts by means of viewing a video of landscape design as a basis for discussion.…”
Section: Evaluation Proceduresmentioning
confidence: 99%
“…Comparable to the study design of Heymann et al (2018), a blinded-randomized analysis of the video material by a total of 56 experts from the fields "Gardening and landscape design" (GL) (n = 17, 3 female Mean age: 26.53 years); "Psychology and psychotherapy" (PP) (n = 15; 9 female; mean age: 23.07) and "Art therapy and Theater Pedagogy" (AT) (n = 24; 18 female; mean age 24.67 years) was conducted. In a first step, the topic of the discussion was introduced to the experts by means of viewing a video of landscape design as a basis for discussion.…”
Section: Evaluation Proceduresmentioning
confidence: 99%
“…Due to the weakness of paper-and-pencil drawing tests and the advancement of technology, digital drawing tests have evolved over the past decade. Digital drawing tests can record and assess drawing characteristics such as total time spent, contour, and drawing methods, which can be considered when discriminating between MCI and dementia (Heymann et al, 2018). Studies showed that on-air movements can enhance the sensitivity of identifying patients with MCI (Garre-Olmo et al, 2017;Müller et al, 2017).…”
Section: Introductionmentioning
confidence: 99%